The crustal structure of Deception Island (West Antarctica) by geophysical data - Levashov, S.; Korchagin, I.; Kozlenko, Yu.; Solovyov, V. (Ukrainian Antarctic Journal, 2006)
New results of the geophysical studies of deep inhomogeneities of crustal structures distribution that were obtained in the SW part of Bransfield Strait near the present Deception Island volcano are discussed. The geophysical data interpretation suggests a local character of the present submarine volcanic activity in the SE part of Deception Island. The magma source is associated with a rather local tectonic disturbance at a depth above 6km. The formation and evolution of this disturbance may caused by features of the distribution of marginal tensions during the interaction of the tectonic continuation of the Hero Fracture Zone and the tectonic disturbances of Bransfield Strait Fracture Zone in the area of Deception Island.